The Undesirable Behaviors Practiced by Faculty Members from the Points of View of Yarmouk University Students: A Survey Study - Muawiah Abu-Ghazal; Naser Magableh & (My University, 2013)
This study aimed at investigating the most common undesirable behaviors of Yarmouk University faculty members. and The Possible differences due to student gender, academic level or faculty. The sample consisted of (1278) undergraduate students (803 female, 475 male), covering all the faculties of Yarmouk university. The results showed that the most common undesirable behaviors among faculty members were: focusing on one method in examinations, presenting much information during one lecture, focusing on subject matter and neglecting practical activates, not to accept student excuses for nonattendance, no concern about students psychosocial problems, not to consider students conditions, tough monitoring students during examinations, bias in students grades, and being moody. The fields of undesirable behaviors were ordered as follows: Evaluation, relationship with faculty members, motivation, class management, teaching methods, personal characteristics, and academic competence. Moreover the results revealed significant differences in the field of teaching methods and faculty, in favor of scientific faculties. Significant differences were found in the field of relationship with faculty members in favor of male students. But in class management, the differences were in favor of female students. Regarding the competence faculty members, significant differences were found due to academic level, and faculty in favor of scientific faculties. Regarding motivation and evaluation, significant differences were founded in favor of humanistic college.

هدفت هذه الدراسة إلى التعرف على أبرز السلوكات غير المرغوبة لدى أعضاء هيئة التدريس من وجهة نظر طلبة جامعة اليرموك، وفيما إذا كانت مجالات هذه السلوكات تختلف باختلاف جنس الطالب وتخصصه الأكاديمي ومستواه الدراسي. تألفت عينة الدراسة من (1278) طالباً وطالبة (475 ذكوراً و803 إناثاً)، من جميع كليات جامعة اليرموك. كشفت النتائج أن أكثر السلوكات غير المرغوبة كانت: التركيز على طريقة واحدة في أسئلة الامتحانات، وإعطاء قدر كبير من المعلومات في المحاضرة الواحدة، والتركيز على المادة الدراسية والتقليل من الأنشطة، والتشدد في الحضور والغياب وعدم قبول أعذار الطلاب، وعدم الاهتمام بالمشاكل الاجتماعية والنفسية للطلبة، وعدم مراعاة ظروف الطلبة، وقسوة التعامل مع الطلبة أثناء الامتحان، وتدخل المحسوبية والواسطة في العلامات، ومزاجية المدرس في التعامل مع الطلبة. كما بينت النتائج أن الترتيب التنازلي لمجالات السلوكات غير المرغوبة لدى أعضاء هيئة التدريس جاء على النحو التالي: التقويم، فالعلاقة مع أعضاء هيئة التدريس، فمجال إثارة الدافعية، ثم إدارة الصف وتنظيمه، ثم طريقة التدريس، فالخصائص الشخصية لعضو هيئة التدريس، وأخيراً الكفاءة الأكاديمية. كما كشفت نتائج الدراسة وجود فروق دالة إحصائياً في مجال طريقة التدريس والكلية لصالح الكليات العلمية، ومتغير المستوى الدراسي لصالح السنة الرابعة والسنة الثالثة. أما في مجال الخصائص الشخصية والعلاقة مع أعضاء هيئة التدريس فقد وجدت فروق لصالح الذكور، لكنها لصالح الإناث في مجال إدارة الصف. أما في مجال كفاءة أعضاء هيئة التدريس، فقد كانت الفروق لصالح السنة الرابعة والثالثة. وفي مجال إثارة الدافعية والتقويم كانت الفروق لصالح الكليات الإنسانية.
السلوكات غير المرغوبة لدى أعضاء هيئة التدريس من وجهة نظر طلبة جامعة اليرموك: دراسة مسحية